Tinjauan Yuridis Tanggung Jawab Hukum dalam Perjanjian Kredit Perbankan Apabila Debitur Wanprestasi - Nuralisha, Marsheila Audrey; Mahmudah, Siti (Fakultas Syariah INSURI Ponorogo, 2023)
Humans are social beings who need each other to achieve what will be achieved. The goal is to communicate thoughts and feelings that arise from his common sense. With the relationship between humans with one another, this can also happen between humans and banks. Which human or someone will lend funds or credit to banks. But in reality, someone who has done credit financing does not follow the agreement and causes default. Thus, the occurrence of this default resulted in a person having to take legal responsibility to resolve the problem. Therefore, This research focuses on the legal principles in default regulations in banking and legal responsibility in resolving default debtor problems. This paper aims to explain the juridical review and legal responsibility in bank credit agreements if the debtor defaults. The research method uses a normative juridical approach that has descriptive characteristics. The result of this study is a juridical review based on the Banking Law and legal responsibility is carried out by mediation first so that the debtor and creditor can choose a middle way. If the debtor cannot resolve the case, then the final solution is to file a lawsuit with the court based on an agreement between the two parties.